The treatment of primary biliary cholangitis: from shadow to light - Sylvia, Drazilova; Tomas, Koky; Marian, Macej; Martin, Janicko; Dagmar, Simkova; Peter, Jarcuska (Therapeutic advances in gastroenterology, 2024)
Primary biliary cholangitis (PBC) is a chronic autoimmune cholestatic disease characterized by the destruction of the small intrahepatic bile ducts, which can progress to liver cirrhosis. The gold standard in the treatment of PBC is ursodeoxycholic acid (UDCA), which is indicated in all patients with PBC because it improves not only biochemical parameters but also patients' survival. An important milestone in the identification of patients at risk is the assessment of biochemical response to UDCA. Patients who respond to treatment have a lower incidence of hepatic events and better prognosis than patients who do not. Several scoring systems can be used to assess the response and identify non-responders who will benefit from second-line treatment. Obeticholic acid (OCA) is currently the only approved second-line treatment for PBC, which is effective for non-responders to UDCA therapy or patients, who have not tolerated UDCA therapy. However, OCA is contraindicated in advanced liver cirrhosis and portal hypertension. Moreover, pruritus may be a limiting factor for the administration of OCA. Fibrates have shown promising data supporting their use in non-responders to UDCA because they improve the biochemical parameters and elastographic findings and have possible antipruritic effects. Therefore, the idea of a triple treatment seems interesting. Clinical research is focusing on several other groups of drugs: peroxisome proliferator-activated receptor (PPAR) δ- and α/δ agonists, non-steroidal farnesoid X receptor agonists, fibroblast growth factor 19 modulators, and inhibitors of nicotinamide adenine dinucleotide phosphate oxidase 1 and 4.